A Study of Economic Efficiency of Utah Dairy Farmers: A System Approach - Kumbhakar, Subal C.; Biswas, Basudeb; Bailey, DeeVon (The Review of Economics and Statistics, 1989)
Subal C. Kumbhakar, Basudeb Biswas, DeeVon Bailey, A Study of Economic Efficiency of Utah Dairy Farmers: A System Approach, The Review of Economics and Statistics, Vol. 71, No. 4 (Nov., 1989), pp. 595-604